Intimate Partner Violence and Depression in Women in China - Yuan, Weiman (Journal of interpersonal violence, 2021)
Intimate partner violence (IPV) is recognized as a major public health and social problem globally, with consequences for the individual, family, and society. But there is relatively little research on IPV in China. The aim of this study was to estimate the prevalence of different types of violence among women and to determine the risk factors and the association with depression. A cross-sectional study among women who had ever been in a relationship was conducted in six provinces across the three regions of China from July to September 2018 using a self-completion questionnaire developed for the study. The provincial capital and one rural county were purposively selected in each province. Questionnaires were distributed in hospitals and public places. The Center for Epidemiologic Studies Depression Scale (CES-D) was used to measure depression. Data for 2,987 women were analyzed. The prevalence of psychological, physical, and sexual violence was 77.7%, 40.2%, and 11%, respectively: 52% had experienced two or three types of violence in their life. After adjustment, risk factors for all-type IPV were low occupational status, having one child or more, living in western provinces, having an income lower than partner’s, and economic pressure. The prevalence of depression was 65.8% in women who experienced psychological violence, 69.5% for physical violence, and 75.8% for sexual violence. For psychological, physical, and sexual violence, the odds ratio for depression were 2.57 (95% confidence interval [CI] = [2.15, 3.07]), 2.07 [1.76, 2.43], and 2.26 [1.73, 2.95], respectively, after controlling for age, occupation, education attainment, and residence. There is a clear need to raise awareness about IPV and to develop approaches for prevention and management. The new Domestic Violence Law represents a step in the right direction.